Online Video Effect as a Learning Media in Improving Speaking Ability English Class X Students of Hang Tuah 4 High School Surabaya Study Year 2017/2018 - Sulistiyani, Sulistiyani; Hidayat, Nur; Sa’aadah, Nuurus (Kontribusia : Research Dissemination for Community Development, 2018)
This research is motivated by the role of language that is very important in the development of science and technology, especially English which is one of the foreign languages that are widely used in every aspect of life such as science, education, culture, business, and entertainment. The author looks at the reality of the lack of mastery of English in the educational environment, especially in the ability to speak. This study aims to describe changes in behaviour after learning English using online video learning media. The theoretical benefit of this research is for the development of science and as a provision for teachers so that it can overcome the problems that occur to students in order to improve the quality of education better. Practical benefits of this research are expected to provide input for English teachers in choosing media as an alternative to improve the quality of learning English and can provide input to teachers in the use of online learning video media for learning English (the ability to speak). The method used in this study is a research method of classroom action with two cycles carried out on the teacher discuss a UK and students of class X SMA Hang Tuah 4 Surabaya. Each cycle consists of stages of planning, action, observation and reflection. Data collection is carried out by testing and non-test. Data analysis is carried out with quantitative and qualitative techniques. Quantitative data analysis is obtained by calculating the overall student value and recapping the test scores, then calculating the average value obtained. The expected results of this study can be concluded that learning by using online video learning media can improve students' speaking ability and can change student behaviour towards positive.